2020
DOI: 10.1186/s12864-020-6607-z
|View full text |Cite
|
Sign up to set email alerts
|

Forcing external constraints on tree inference using ASTRAL

Abstract: Background: To account for genome-wide discordance among gene trees, several widely-used methods seek to find a species tree with the minimum distance to input gene trees. To efficiently explore the large space of species trees, some of these methods, including ASTRAL, use dynamic programming (DP). The DP paradigm can restrict the search space, and thus, ASTRAL and similar methods use heuristic methods to define a restricted search space. However, arbitrary constraints provided by the user on the output tree c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…We hypothesize that the relationships involving the two taxa interacted with other regions of the tree in such a manner that their unconventional positions increased global quartet support despite decreasing it locally. This phenomenon was recently noted by Rabiee and Mirarab (2020), who showed that constrained ASTRAL searches can reveal well-supported clades absent from the main ASTRAL tree at the cost of decreasing the overall quartet score. As a result, we do not consider the relationships of Dromas and Pluvianus to represent genuine instances of gene tree/species tree discordance, but their different resolutions in the species-tree and concatenated analyses may indicate the presence of such conflict in neighboring regions of the tree.…”
Section: Congruence and Conflict In Higher-level Charadriiform Relationshipsmentioning
confidence: 57%
“…We hypothesize that the relationships involving the two taxa interacted with other regions of the tree in such a manner that their unconventional positions increased global quartet support despite decreasing it locally. This phenomenon was recently noted by Rabiee and Mirarab (2020), who showed that constrained ASTRAL searches can reveal well-supported clades absent from the main ASTRAL tree at the cost of decreasing the overall quartet score. As a result, we do not consider the relationships of Dromas and Pluvianus to represent genuine instances of gene tree/species tree discordance, but their different resolutions in the species-tree and concatenated analyses may indicate the presence of such conflict in neighboring regions of the tree.…”
Section: Congruence and Conflict In Higher-level Charadriiform Relationshipsmentioning
confidence: 57%
“…Compared to the wASTRAL-h tree it differed in 8 branches, and compared to the TENT and MP-EST* tree it differed in 9 and 8 branches. The ASTRID tree also did not recover the Columbea clade, a clade that has seen strong support in various analyses of this data [12, 52, 36].…”
Section: Resultsmentioning
confidence: 86%
“…The second technique operates by replacing the constraint set that ASTRAL computes from the input with a smaller constraint set. One such approach uses "external constraints", for example partial information about the species tree, in order to reduce the constraint set size (Rabiee and Mirarab, 2020a), an approach we refer to as "ASTRAL-J" to reflect the flag used in ASTRAL for this case. Another approach runs ASTRID on a collection of subsamples of the gene trees, so that each ASTRID analysis of each subsample produces a candidate species tree.…”
Section: Species Tree Estimation In the Presence Of Ilsmentioning
confidence: 99%